An aniline dication-like transition state in the Bamberger rearrangement - Yamabe, Shinichi; Zeng, Guixiang; Guan, Wei; Sakaki, Shigeyoshi (Beilstein journal of organic chemistry, 2013)
A Bamberger rearrangement of N -phenylhydroxylamine, Ph–N(OH)H, to p -aminophenol was investigated by DFT calculations for the first time. The nitrenium ion, C 6 H 5 –NH + , suggested and seemingly established as an intermediate was calculated to be absent owing to the high nucleophilicity of the water cluster around it. First, a reaction of the monoprotonated system, Ph–N(OH)H + H 3 O + (H 2 O) n ( n = 4 and 14) was examined. However, the rate-determining transition states involving proton transfers were calculated to have much larger activation energies than the experimental one. Second, a reaction of the diprotonated system, Ph–N(OH)H + (H 3 O + ) 2 (H 2 O) 13 , was traced. An activation energy similar to the experimental one was obtained. A new mechanism of the rearrangement including the aniline dication-like transition state was proposed.